Experiences of imprisoned women about health actions provided in the prison system - Araújo Moreira, Michelle; Santos Souza, Hozana (O Mundo da Saúde, 2014)
Health actions provided in the prison system have been questioned by managers, educators and professionals from various fields, especially because of the growth in the female imprisoned population. This article discusses the experiences of imprisoned women about health actions provided in the prison system. It is a qualitative, descriptive and exploratory research conducted with 11 women prisoners in the penal complex of a city of Bahia State, in the closed regime, irrespective of criminal conduct. To collect data, we administered semi-structured interviews between February and April 2013, and the testimonials decoded by content analysis. Data analysis highlighted aspects related to the (in) existence and/or (in) effectiveness of health interventions provided to women in the prison system and an interference with participation in the production of self-care. It was concluded that there is a need for effective public policies directed to women prisoners, as it emphasizes the importance of a multidisciplinary team committed to effective health care.